(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Mold infestation in oil seeds like groundnuts results in significant quantitative and qualitative losses, typically managed with chemical treatments posing risks to humans, animals, and the environment. Prioritizing effective biological controls with presumed lower risks, this study explored selenium biosynthesized nanoparticles as antifungal agents against Aspergillus flavus and Penicillium sp. in groundnuts. Standard methods identified the spoilage molds, while Cassia fistula leaf extract facilitated the biosynthesis of selenium nanoparticles. Biosynthesized Selenium Nanoparticles (CFSNPs) were characterized using UV-visible spectroscopy, Transmission Electron Microscope (TEM), Fourier Transform Infra-Red (FTIR) spectrometry, and Energy Dispersive X-ray (EDX). The stabilized CFSNPs exhibited a brownish color with a UV-visible absorption peak at 450 nm, indicating SeNP formation. TEM micrographs revealed spherical, cubic, rod, and irregularly shaped CFSNPs with clusters, while EDX spectra showed selenium (Se) as the predominant element (80.76% by weight). FTIR peaks at 4400, 3173.00, 2361.44, 1594.00, 1373.00, 1027.29, and 674.23 cm-1 confirmed characteristic vibrations. Antifungal assays demonstrated CFSNPs’ efficacy, inhibiting fungal mycelial growth by 75.1% and 95.12% against A. flavus, and 71.5% and 86.25% against Penicillium species at concentrations of 0.75 mg/ml and 1.0 mg/ml, respectively. In comparison, Cassia leaf extract exhibited lower inhibitory activity against A. flavus (20.8%, 35.6%) and Penicillium spp. (23.1%, 40.6%) at similar concentrations. The antifungal properties of CFSNPs suggest potential applications in preserving agro-produce, thereby extending the shelf life of oil seed crops.